Magnetic Property and GMI Effect of MFe2O4 Nanoparticles - Lam, Dao Son; Ngo, Huong Thu (VNU Journal of Science: Mathematics - Physics; Vol 33 No 2, 2017)
Abstract: In the present article, we report the biosensor can detect superparamagnetic nanoparticles (less than 10 nm in size) at various and low particle concentrations, which is of the importance role in biosensing applications. The nanoparticle ferrite (Fe 3 O 4 ), Cobalt ferrite (CoFe 2 O 4 ), Nickel ferrite (NiFe 2 O 4 ) nanoparticles were synthesized by the high temperature thermal decomposition precursor method. The saturation of magnetization have significantly increased as the 12 ± 1 nm Fe 3 O 4 (40 emu/g), 6 ± 0.5 nm NiFe 2 O 4 (57 emu/g) and 7 ± 0.5 nm CoFe 2 O 4 (88.6 emu/g) nanoparticles. The saturation magnetization of CoFe 2 O 4 nanoparticle is larger than NiFe 2 O 4 , Fe 3 O 4 nanoparticle. The sensitivity of biosensor depend on saturation magnetization of nano particles, thus we have performed a systematic study of the longitudinally excited magneto-inductance effect of an inductive coil with CoFe 2 O 4 nanoparticles is in its core. Our results show that the ([D X / X ]) ratios and field sensitivity increase. These results are of practical importance in designing novel magnetic sensors based on the LEMI effect for sensing applications.